Second homes in Tyrol - Axel Borsdorf (Revue de Géographie Alpine)
Second homes are quite popular in the Alps. Many people living in urban agglomerations endeavor to spend part of their time in fresh nature and a beautiful landscape and to participate in local culture. The drawbacks for alpine communities are obvious: free space is overbuilt, costs for infrastructure are rising, the second homes with their over long periods closed window shutters transmit the image of “dead villages”. The hotels suffer by the completion of the sublease of second homes. On the other hand alpine municipalities attain financial means by selling lots, which can be invested in infrastructure and for the maintenance of touristic competitiveness. Second homes sustain the construction industry and the retail trade. The disadvantages of second homes led to restrictive measures in the Austrian Federal State of Tyrol. They partly disagree to European laws and even to the constitution of Austria. In spite of these restrictions the percentage of people living part of their time in second homes has remarkably increased in Tyrolean communities during the last years. This demonstrates that regulation measurements are not as effective as they intended to be. This article illustrates the development of the second home sector in Tyrol, its connection to the phenomenon of multilocality, documents the legal conditions and tries to give an evaluation.